2024
DOI: 10.1136/rmdopen-2023-003809
|View full text |Cite
|
Sign up to set email alerts
|

Difficult-to-treat psoriatic arthritis (D2T PsA): a scoping literature review informing a GRAPPA research project

Shikha Singla,
Andre Ribeiro,
Murat Torgutalp
et al.

Abstract: BackgroundPsoriatic arthritis (PsA) is a multifaceted condition with a broad spectrum of manifestations and a range of associated comorbidities. A notable segment of patients with PsA remains resistant to even advanced therapeutic interventions. This resistance stems from myriad causes, including inflammatory and non-inflammatory factors.ObjectivesTo collate and critically assess the various definitions and criteria of difficult-to-treat (D2T PsA present in the literature.MethodsUsing the Preferred Reporting I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Similarly, Wendling et al [ 28 ] advocated for a comparable approach in delineating D2T-axSpA, proposing the failure of either ≥2 b/tsDMARDs with different MOAs or ≥3 b/tsDMARDs regardless of their MOA, as criteria. However, as recently illustrated by a scoping review carried by our research team, there is still no consensus regarding the number of drugs that a patient must fail to be classified as D2T-PsA [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wendling et al [ 28 ] advocated for a comparable approach in delineating D2T-axSpA, proposing the failure of either ≥2 b/tsDMARDs with different MOAs or ≥3 b/tsDMARDs regardless of their MOA, as criteria. However, as recently illustrated by a scoping review carried by our research team, there is still no consensus regarding the number of drugs that a patient must fail to be classified as D2T-PsA [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) has initiated a key project to define ‘difficult-to-treat’ psoriatic arthritis (D2T-PsA). This initiative began with a scoping review to understand existing definitions and applications of D2T-PsA in the literature [ 10 ]. An important outcome of this review was the introduction of the term ‘complex-to-manage psoriatic arthritis’ (C2M-PsA), which encompasses inclusion of factors such as depression, fatigue and comorbidities that can contribute to persistence of negative symptoms or treatment limitations.…”
Section: Introductionmentioning
confidence: 99%
“…56 In a recent systematic literature review performed by GRAPPA, the definitions found for D2T PsA were variable across the studies: in some cases, this was vaguely described as multiple treatment attempts, while in others it covered from failure to ≥1 TNFi to failures involving ≥2 b/tsDMARDs or even extending to ≥3 b/tsDMARDs. 42 An EULAR survey conducted in 2023 among specialist rheumatologists revealed varied opinions concerning the criteria for defining D2T PsA. 40 The majority of respondents (34.8%) supported a definition of D2T PsA that involved the failure of at least 2 classes of b/tsDMARDs with a pragmatic definition of truly 'refractory PsA' being preferred, indicating 'failing all available classes of b/tsDMARDs' (74%).…”
Section: Difficult-to-treat Psamentioning
confidence: 99%
“…[ 40 ] Indeed, comorbidities and widespread pain contribute to complicated management of patients (what can be term ‘difficult to manage’. [ 41 , 42 ] This emphasizes the need to address both inflammatory and non-inflammatory factors for optimal PsA management, with consideration of all comorbidities in therapeutic decisionmaking. [ 43 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation